Study of Quality and Structure of Education in Modern India (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Education in modern India has undergone significant transformations over the past few decades. With advancements in technology, policy reforms, and increased focus on inclusive and equitable education, the landscape of Indian education continues to evolve. This paper examines the current state of education in India, highlighting key reforms, challenges, and future directions. By analyzing various aspects of primary, secondary, and higher education, this paper aims to provide a comprehensive understanding of the progress and ongoing efforts to improve the educational system in India.